2016
DOI: 10.1155/2016/6869154
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic Acid Based Nanocomposites: Promising Safe and Biodegradable Materials in Biomedical Field

Abstract: Polylactic acid (PLA) is widely used in biological areas due to its excellent compatibility, bioabsorbability, and degradation behavior in human bodies. Pure polylactic acid has difficulty in meeting all the requirements that specific field may demand. Therefore, PLA based nanocomposites are extensively investigated over the past few decades. PLA based nanocomposites include PLA based copolymers in nanometer size and nanocomposites with PLA or PLA copolymers as matrix and nanofillers as annexing agent. The sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 120 publications
(127 reference statements)
0
49
0
3
Order By: Relevance
“…Depending on the composition of the optically active l - and d , l -enantiomers, PLA can crystallize in three forms (α, β, and γ). Thorough understanding of the intrinsic structural, thermal, and physicochemical properties of PLA polymers along with the knowledge of how such properties can be tuned and manipulated with nanomaterials have fueled remarkable biotechnological interest in PLA nanocomposites [ 4 , 5 , 6 ]. The extensive review by Södergårt and Stold [ 7 ] presents different polymerization schemes associated with lactic acid chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the composition of the optically active l - and d , l -enantiomers, PLA can crystallize in three forms (α, β, and γ). Thorough understanding of the intrinsic structural, thermal, and physicochemical properties of PLA polymers along with the knowledge of how such properties can be tuned and manipulated with nanomaterials have fueled remarkable biotechnological interest in PLA nanocomposites [ 4 , 5 , 6 ]. The extensive review by Södergårt and Stold [ 7 ] presents different polymerization schemes associated with lactic acid chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their good biocompatibility, the PLA-based materials were extensively used in the field of tissue engineering. However, in order to obtain better optimized scaffolds and to increase cell proliferation and cell adhesion on their surface, PLA have been mixed with other polymers, such as collagen, gelatin or graphene oxide [44,45]. For instance, Qiao et al [45] found that PLA/collagen electrospun fibrous scaffolds at a 60:40 weight ratio showed greatest stability, cell attachment, cell proliferation, and osteogenic differentiation of bone marrow stromal cells after five-week culture period.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-adhesion materials, patch, drug-delivery carrier, bone-fixing device, suture, tissue-engineered scaffold [40][41][42] Biocompatibility, good mechanical properties, safe, non-toxic [40][41][42] Poor toughness, degradation speed slow, hydrophobicity, lack of reactive side chain groups [40][41][42] Polyurethane Excipients, medical bandage [43][44][45] Low cost, rich resource, good mechanical properties [43,44,46,47] Degradation speed slow [43,46,47] Poly(lactic-glycolic acid) (PLGA)…”
Section: Chitosanmentioning
confidence: 99%